Bio-guided isolation of anti-leishmanial natural products from Diospyros gracilescens L. (Ebenaceae) - Cyrille Armel N. Njanpa; Steven Collins N. Wouamba; Lauve Rachel T. Yamthe; Darline Dize; Brice Mariscal T. Tchatat; Patrick Valère F. Tsouh; Michel Nguiam Pouofo; Jean Bosco Jouda; Bruno Lenta Ndjakou; Norbert Sewald; Simeon Fogue Kouam; Fabrice Fekam Boyom (BMC, 2021)
Abstract Background Plants represent an intricate and innovative source for the discovery of novel therapeutic remedies for the management of infectious diseases. The current study aimed at discovering new inhibitors of Leishmania spp., using anti-leishmanial activity-guided investigation approach of extracts from Diospyros gracilescens Gürke (1911) (Ebenaceae), targeting the extracellular (promastigotes) and intracellular (amastigotes) forms of Leishmania donovani. Methods The plant extracts were prepared by maceration using H20: EtOH (30:70, v/v) and further fractionated using a bio-guided approach. Different concentrations of D. gracilescens extracts, fractions and isolated compounds were tested in triplicate against L. donovani promastigotes and amastigotes in vitro. The antileishmanial potency and cytotoxicity on RAW 264.7 cells were determined using the resazurin colorimetric assay. The time kill kinetic profile of the most active sample was also investigated. The structures of all compounds were elucidated on the basis of extensive spectroscopic analyses, including 1D and 2D NMR, and HR-ESI-MS and by comparison of their data with those reported in the literature. Results The hydroethanolic crude extract of D. gracilescens trunk showed the most potent antileishmanial activity (IC50 = 5.84 μg/mL). Further fractionation of this extract led to four (4) fractions of which, the hexane fraction showed the most potent activity (IC50 = 0.79 μg/mL), and seven (07) compounds that exhibited moderate potency (IC50 = 13.69-241.71 μM) against L. donovani. Compound 1-deoxyinositol (7) inhibited the promastigote and amastigote forms of L. donovani with IC50 values of 241.71 μM and 120 μM respectively and also showed the highest selectivity against L. donovani promastigotes (SI > 5.04). To the best of our knowledge, the antileishmanial activity of this compound is being reported here for the first time. The promising hexane fraction showed significant inhibition of parasites growth at different concentrations, but with no evidence of cidal effect over an exposure period of 120 h. Conclusions The results obtained indicated that the hydroethanolic extract from the D. gracilescens trunk and the derived hexane fraction have very potent inhibitory effect on cultivated promastigotes and amastigotes of L. donovani parasite. The isolated compounds showed a lesser extent of potency and selectivity. However, further structure-activity-relationship studies of 1-deoxyinositol could lead to more potent and selective hit derivatives of interest for detailed drug discovery program against visceral leishmaniasis.